Improving Quality Education Based on Quality Management and Character Based Education - Rivauzi, Ahmad (Jurnal Kawakib, 2023)
This paper describes how to improve the quality of education. This research is library research, analyzed qualitatively because there is an interest in interpretation and seeking meaning from written texts in literary sources. Schools must play a role in helping students learn about values so that they know and can understand good values, schools must stimulate and foster students' moral awareness so that they have an awareness of values, and schools must also provide space, assistance, and supervision to students to do and work on good values. Quality management and organizational commitment are very important related to the quality of education. In the Quran, the word commitment corresponds to the word إعتصام which can be found 14 times in repetition in several verses and letters and can be interpreted as maintaining, protecting, or holding fast (istamsaka). Management is synonymous with the word "dabbara, Yudabbiru, tadbiran" which means to direct, manage, implement, run, regulate and take care of. Quality is the realization of the principle of ihsan(احسان), in the form of giving goodness to anything and anyone, and avoiding damage in any form Improving the quality of education can be done by increasing the role of schools and educational institutions with a strategy of preparing character leadership, human resource development, and character-based education.